2010
DOI: 10.1016/j.jaac.2010.07.007
|View full text |Cite
|
Sign up to set email alerts
|

National Trends in Child and Adolescent Psychotropic Polypharmacy in Office-Based Practice, 1996-2007

Abstract: Objective To examine patterns and recent trends in multi-class psychotropic treatment among youth visits to office-based physicians in the United States. Method Annual data from the 1996–2007 National Ambulatory Medical Care Surveys were analyzed to examine patterns and trends in multi-class psychotropic treatment within a nationally representative sample of 3466 child and adolescent visits to office-based physicians in which a psychotropic medication was prescribed. Results There was an increase in the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
218
3
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(227 citation statements)
references
References 62 publications
(61 reference statements)
4
218
3
2
Order By: Relevance
“…However, studies have shown that a high proportion of prescriptions for psychotropic medications such as anxiety medications fail to have a corroborating diagnosis in the medical record. [15][16][17] Our data do not allow confirmation via medical records or other sources.…”
Section: Discussionmentioning
confidence: 97%
“…However, studies have shown that a high proportion of prescriptions for psychotropic medications such as anxiety medications fail to have a corroborating diagnosis in the medical record. [15][16][17] Our data do not allow confirmation via medical records or other sources.…”
Section: Discussionmentioning
confidence: 97%
“…36,37 Antipsychotic use, in particular, has shown large increases. 38 Especially notable is their burgeoning off-label use, [39][40][41] including in preschool-aged children.…”
Section: Adverse Effects Of Psychiatric Medicationsmentioning
confidence: 99%
“…A variety of psychoactive medications are also used frequently for these patients. In fact, a national study indicates that the most common problem category for children receiving psychoactive medications in the USA is DBPs (including ADHD) [31] and national "best practice" recommendations include prescription of psychoactive medications for these youths [32]. Efficacy research data offer promising support for the use of psychoactive medications for children with DBPs, particularly stimulant medication for children with attention and hyperactivity symptoms, which often occur concurrently with other DBPs [33].…”
Section: Children With Disruptive Behavior Problemsmentioning
confidence: 99%
“…There is significant national attention to the increased use of psychoactive medications for children [10,36] with public controversy about rising rates of use of psychoactive medications for children, including increasing rates of polypharmacy [31] and potential health risks. Several medications are recommended as "best practices," but there is considerable debate about potential over-and/or under-use and concern about unintended effects of several different psychoactive medications used to treat DBPs in childhood.…”
Section: Children With Disruptive Behavior Problemsmentioning
confidence: 99%
See 1 more Smart Citation